¿Cómo integrar la educación para el trabajo y el desarrollo humano (ETDH) con el Sistema de Educación Formal de Colombia? - Lesmes Quintero, Paola Andrea (Universidad Santo Tomás, 2017)
This research aims to understand differences and divergences, which are presented in the Colombian educational system from the Education for Work and Human Development (EDTH). This is done having three dimensions; first, the historical part of non-formal education, technical education from colonial times until our days, presenting a view from the following parts: political, social, economic and educational. In addition to review some international cases of this type of education, such as The Americas and the Caribbean, Mexico and Uruguay. Another dimension has consisted of conducting a legislative review of education in arts and crafts, technical, and non-formal. This review was performed from the first Education Act, Act 39 of 1903 and its Regulatory Decree 491 of 1904, where they align with the Constitution of 1886, to the current legislation, Law 1064 of 2006 and Decree 4904 of 2009, in which guidelines for the establishment, organization and functioning of institutions and ETDH programs are established. Among other requirements, it determines that an EDTH program must develop job skills referred in the National Occupational Classification. It also establishes two types of certifications associated with the fulfillment of programs: the Certificate of Technical Labor by competences and Certificate of Academic Skills. And the last but not least dimension, the study of the official discourse on the ETDH to highlight the differences and divergences between the theoretical discourse prepared for the ETDH and the existing public policy. This has become inputs to design a proposal to eliminate differences and divergences found between the legislation and official discourse, thereafter to integrate the ETDH to the instruction chain of the Colombian educational system. The proposal is structured in three d ifferent perspectives: The first one consists in a change in legislation, which begins with changing the name of the Education for Work and Human Development for Professional Education and Training, among other provisions that seek to give a relevant and consistent position on this type of education, and be clear about the requirements to provide the service; on the other hand, achieve an articulation that will allow to find effective solutions to the demands of the labor market and therefore give relevance to programs, skills, abilities and profiles required by students to enter the workforce and be recognized as members that provide to the company through their knowledge and performance. The second perspective is a process of dissemination, socialization of Professional Education and Training, where it is addressed what it is, its advantages, purposes, degrees, certificates and articulation processes of Professional Education and training, and the Secondary and Higher Education, among other aspects. Finally, it must be established a monitoring system to ensure compliance with the rules generated for The Professional Education and Training, developed by control agencies such as the Department of District Education (SED), as the Education institutions, the Ministry of National Education of Colombia (MEN), on arrangements, and supervision of the SED and local.